Analisis Kemampuan Guru Dalam Melaksanakan Penilaian Kurikulum 2013 Di SDIT Muhammadiyah Al-Kautsar Tahun 2016/2017 - Hidayatulloh, Syarif; , Drs. Suwarno, SH., M.Pd (2017)
This study aims to describe (1) the implementation of the 2013 curriculum assessment at SDIT Muhammadiyah Al-Kautsar, (2) the ability of teachers to carry out the assessment of the 2013 curriculum in SDIT Muhammadiyah Al-Kautsar, (3) teacher constraints in implementing the 2013 curriculum assessment. Is a type of qualitative research and uses phenomenological research design. Data collection techniques use observation, interviews, and documentation. Data analysis techniques with data collection, data reduction, data presentation, and conclusions. The validity of the data in this study using triangulation techniques and source triangulation. The results of this study are (1) in the implementation of the 2013 curriculum assessment at SDIT Muhammadiyah Al-Kautsar has been running well, but there is still something to be improved especially from the problem of implementation time, (2) the teacher's ability in the implementation of the 2013 curriculum assessment at SDIT Muhammadiyah Al- Kautsar is good and able to master the assessment of curriculum 2013 well, (3) in the implementation of 2013 curriculum assessment there are some barriers that is the problem of time and the number of students and aspects that must be assessed make the teacher difficulty in the implementation.